PENGARUH KARAKTERISTIK PEMERINTAH DAERAH, HASIL PEMERIKSAAN AUDIT DAN PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KOTA LANGSA - Safira Amalia; Nurlina; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
This study aims to determine the characteristics of local government, audit results and local revenue on the financial performance of the local government of Langsa City. The population and research sample are the financial statements of Langsa City for the years 2006-2020 contained in the Langsa City BPKD. The results of this study partially show that the characteristics of local governments have a significant value of 0.739 > 0.05. The results show that there is no significant effect on the financial performance of local governments. The results of the audit have a significant value of 0.367 > 0.05. The results show that there is no significant effect on the government's financial performance. region, and local revenue has a significant value of 0.058 > 0.05. The results show that it has no significant effect on the financial performance of local governments. Simultaneous research results show that the characteristics of local government, audit results, and local revenue have an effect of 40.8% on the financial performance of local governments.